Effect of sloppy sample preparation on results from uniaxial compressive strength tests. Issue 1 (August 2021) - Koelen, K; Alber, M; Duda, M; Backers, T
Abstract: The requirements on sample geometry for strength tests are specified in standards and recommendations such as those provided by ASTM, ISRM and DGGT. Various circumstances may lead to deviations from these specifications, e.g., the nature of the rock material, lack of time, economic reasons, underestimation of the importance of precise preparation and inaccurate tools. We investigated the effect of sloppy sample preparation on the experimentally determined Young's modulus and uniaxial compressive strength in conventional uniaxial compressive strength tests of two rocks, Ruhr sandstone and Solnhofen limestone. Both are known for their high uniaxial compressive strength > 100 MPa and Young's modulus > 30 GPa. Six end face geometry categories were tested on cylindrical samples with a diameter of 30 mm and a nominal length of 65 mm: (1) two standard end faces with tolerances ± 0.01 mm and ± 0.005 mm, (2) one standard, one inclined end face with inclinations of 0.04°, 0.1°, 0.6° and 1.2°, (3) two inclined end faces with inclinations of 0.04° and 0.6° and three azimuth combinations, (4) two rough end faces, (5) two wedged end faces with wedge angles of 5° and 10°, and (6) two spherical end faces with radii of 35 mm, 40 mm, and 45 mm. At least two samples were tested for one geometry. The strength for standard end face geometries based on seven tests was 171±9 MPa for Ruhr sandstone and 232±38 MPa for Solnhofen limestone. Low tolerance standard end faces showed a slightly better reproducibility than high tolerance standard end faces. The strength of Ruhr sandstone reduced significantly by 61% from 181±20 MPa to 70±7 MPa when the inclination of one end face was increased. For the same geometries, the strength of Solnhofen limestone reduced by 71%. The full ranges of strength and Young's modulus (excluding spherical geometries which were determined only for Ruhr sandstone) were 27 MPa to 266 MPa and 2 GPa to 48 GPa for Solnhofen limestone, and 70 MPa to 351 MPa and 3 GPa to 41 GPa for Ruhr sandstone. Our results show that low tolerance preparation increases reproducibility, and slight deviations from standard end face geometries and impurities significantly affect experimentally determined Young's modulus and strength.